(untitled) (Biological Sciences - PJSIR, 2001)
For drawing a quantitative picture of Swat vegetation, 21 quadrats (stands) (1Ox10 m for arboreal vegetation and 2x2 m for herbs and shrubs) were studied. On the basis of importance value, twenty one plant communities were established and computerized cluster analysis of 267 species was carried out. One stand showed greatest diversity. Five stands were slightly different from each other whereas six stands were closely related.